2014
DOI: 10.3329/bjas.v43i2.20718
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of carcass and meat characteristics between male and female indigenous rabbit of Bangladesh

Abstract: This experiment was conducted to determine and compare some characteristics of the meat and carcass of rabbit aged 6 months according to sex. In the experiment six male and six female nondescript rabbits were slaughtered. The weight and percentage of warm carcasses, skin with head and limbs, liver, kidney, heart, lung, forelegs, hind legs, breast and ribs, loin and abdominal wall were recorded. The values for carcass length, lumbar circumference, drip loss, cooking loss, sensory characteristics were also deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 15 publications
(22 reference statements)
1
12
1
Order By: Relevance
“…Fayeye and Ayorinde (2008); Ghosh and Mandal (2008) and Yalçın et al (2006) reported that sex had no significant effects on the slaughter weight of New Zealand rabbits at 11 weeks. This report is however contrary to the reports of other authors; Adelodun (2015) who recorded higher significant (P<0.05) values female than male rabbits, while Murshed et al (2014) and Trocino et al (2002) recorded higher significant (P<0.05) values male than female rabbits. The mean values obtained for preslaughter and hot carcass weights in this study were however lower than those obtained by Adelodun (2015) who reported 2220.60±71.2 g and 2088.70±11.5 g for male and female respectively on pre-slaughter weights and 2150±14.13 g and 2023.91±15.59 g for male and female respectively on hot carcass weights.…”
Section: Resultscontrasting
confidence: 98%
See 2 more Smart Citations
“…Fayeye and Ayorinde (2008); Ghosh and Mandal (2008) and Yalçın et al (2006) reported that sex had no significant effects on the slaughter weight of New Zealand rabbits at 11 weeks. This report is however contrary to the reports of other authors; Adelodun (2015) who recorded higher significant (P<0.05) values female than male rabbits, while Murshed et al (2014) and Trocino et al (2002) recorded higher significant (P<0.05) values male than female rabbits. The mean values obtained for preslaughter and hot carcass weights in this study were however lower than those obtained by Adelodun (2015) who reported 2220.60±71.2 g and 2088.70±11.5 g for male and female respectively on pre-slaughter weights and 2150±14.13 g and 2023.91±15.59 g for male and female respectively on hot carcass weights.…”
Section: Resultscontrasting
confidence: 98%
“…There were no effects of sex on the results obtained for the primal cut parts in this study. This report is similar to the report of; Baiomy and Hassanien (2011); Fayeye and Ayorinde (2008); Ghosh and Mandal (2008); Murshed et al (2014), who recorded non-significant difference effects of sex on different primal cuts of rabbit carcass. Yalçin et al (2006) also observed that sex had no effects in the weights and percentages of fore legs, hind legs, ribs and loin.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…It contains an abundance of iron, potassium and fatty acids, which play a major role in the proper functioning of the human body [13,14]. Goat meat has a nutritional value similar to that of sheep meat [15], but its fine-fibre structure makes it easier to digest. Due to the low content of saturated fatty acids and cholesterol and a high concentration of polyunsaturated fatty acids, as well as the presence of valuable amino acids such as lysine, threonine and tryptophan, goat meat can be a healthier alternative to other red meat varieties [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…The lamb meat is one of the best options for consumers for which they are willing to pay high; however, it fails in gaining market space due to the lack of standardization and quality when it reaches to the consumer (Cirne et al, 2018). Meat quality and price are affected by carcass weight and it is essential to understand the various elements that can influence the primary qualities of meat and carcass quality in this context (Murshed et al, 2014;Moniruzzaman et al, 2002;Kawsar et al, 2006). Age (Barone et al, 2007), sex (Horcada et al, 1998), breed (Crouse et al, 1981) and feed type (Hopkins & Fogarty, 1998) have been found some effects on carcass weight, conformation, fat content, and pH, texture, instrumental color, and nutritional composition.…”
Section: Introductionmentioning
confidence: 99%